Transcriptional profiling of shell calcification in bivalves - Yarra, Tejaswi (The University of Edinburgh, 2018)
Mollusc shells are unique adaptations that serve to protect the organisms that make them, and are a defining feature of the phylum. However the molecular underpinnings of shell forming processes are still largely unexplored. To further understand mollusc shell formation, I studied three bivalve species in this project: the blue mussel Mytilus edulis, the Pacific oyster Crassostrea gigas, and the king scallop Pecten maximus. While previous analyses of the shell proteomes showed species specificity, transcriptomes of the mantle tissues revealed more commonalities. To reconcile these differences, I studied differential gene expression in shell damage-repair experiments and during the formation of the first larval shell, to produce a comprehensive overview of shell formation processes. Expression data showed large biological variability between individuals, requiring matched-pair experimental designs to detect differential gene expression during shell repair. Loci differentially expressed during shell repair and in the larvae encoded shell matrix proteins, transmembrane transporters, and novel transcripts. A large number of shell matrix proteins, encoded in differentially expressed loci, were common in all three species during shell formation, indicating that shell forming proteins between different species may be more common than previously thought. Differential expression of transmembrane transporters during shell repair indicated that the animals may be regulating bicarbonate ions during shell formation. Finally, the experiments revealed novel transcripts, with unknown annotations to public datasets, that may putatively be involved in shell formation.